Legal Effectiveness of Restorative Justice Criteria Application in Resolving Small-Scale Village Fund Irregularities - Muhammad Zainul Arifin; Dewi Kania Sugiharti; Indra Perwira (Jurnal Studi Sosial dan Politik, 2024)
Small-scale Village Fund mismanagement constitutes a distinct legal issue requiring proportional handling between two main options: conventional criminal law or restorative justice mechanisms. This study aims to examine two main issues: first, the legal effectiveness of the application of restorative justice criteria by Law Enforcement Officials (APH) in resolving cases of small-scale Village Fund mismanagement; and second, the ideal boundaries between the jurisdictions of state administration and criminal law in the implementation of restorative justice in Village Fund management. This study uses a combined normative-empirical legal research method by analyzing applicable laws and regulations, court decisions, APH policies, and case resolution practices in the field. The analytical framework is based on Soerjono Soekanto's theory of legal effectiveness and Howard Zehr's theory of restorative justice. The results of the study indicate that the effectiveness of restorative justice implementation remains at a suboptimal level due to the inadequate fulfillment of the four factors of legal effectiveness: substance, structure, culture, and means. Meanwhile, the boundaries between administrative and criminal law cannot be determined solely by the value of state losses, but must comprehensively consider the elements of mens rea, the substantive impact on village development, and the intention to restore. This study recommends the formation of joint technical regulations between law enforcement agencies and the development of an operational decision-making matrix in handling cases of Village Fund misappropriation.